Bordetella Adenylate Cyclase Toxin Elicits Airway Mucin Secretion through Activation of the cAMP Response Element Binding Protein - Malandra, Anna; Rahman, Waheed Ur; Klimova, Nela; Streparola, Gaia; Holubova, Jana; Osickova, Adriana; Bariselli, Simone; Sebo, Peter; Osicka, Radim (International journal of molecular sciences, 2021)
The mucus layer protects airway epithelia from damage by noxious agents. Intriguingly, Bordetella pertussis bacteria provoke massive mucus production by nasopharyngeal epithelia during the initial coryza-like catarrhal stage of human pertussis and the pathogen transmits in mucus-containing aerosol droplets expelled by sneezing and post-nasal drip-triggered cough. We investigated the role of the cAMP-elevating adenylate cyclase (CyaA) and pertussis (PT) toxins in the upregulation of mucin production in B. pertussis-infected airway epithelia. Using human pseudostratified airway epithelial cell layers cultured at air-liquid interface (ALI), we show that purified CyaA and PT toxins (100 ng/mL) can trigger production of the major airway mucins Muc5AC and Muc5B. Upregulation of mucin secretion involved activation of the cAMP response element binding protein (CREB) and was blocked by the 666-15-Calbiochem inhibitor of CREB-mediated gene transcription. Intriguingly, a B. pertussis mutant strain secreting only active PT and producing the enzymatically inactive CyaA-AC- toxoid failed to trigger any important mucus production in infected epithelial cell layers in vitro or in vivo in the tracheal epithelia of intranasally infected mice. In contrast, the PT- toxoid-producing B. pertussis mutant secreting the active CyaA toxin elicited a comparable mucin production as infection of epithelial cell layers or tracheal epithelia of infected mice by the wild-type B. pertussis secreting both PT and CyaA toxins. Hence, the cAMP-elevating activity of B. pertussis-secreted CyaA was alone sufficient for activation of mucin production through a CREB-dependent mechanism in B. pertussis-infected airway epithelia in vivo.
Keywords: Cell Line; epitelové buňky; mucin; Mice, Inbred BALB C; Mucin 5AC; adenylate cyclase toxin; Cyclic AMP Response Element-Binding Protein; Epithelial Cells; Whooping Cough; Mice; mucin 5AC; epithelium; cAMP; CREB; Bordetella; Bordetella pertussis; pertuse; zvířata; Humans; myši inbrední BALB C; protein vázající cAMP responzivní element; myši; pertussis toxin; adenylátcyklasový toxin; Adenylate Cyclase Toxin; buněčné linie; Respiratory System; dýchací soustava; lidé; Animals